Karakteristrik Enkapsulat Pewarna dari Ekstrak Daun Pepaya (Carica papaya L.) pada Perlakuan Perbandingan Gelatin dan Maltodekstrin - Aditya, Samapta Manggala; Wrasiati, Luh Putu; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): MaretDO - 10.24843/JRMA.2021.v09.i01.p05, 2021)
Papaya leaves can be used as a green dye because it contains chlorophyll. Chlorophyll compounds as a green coloring are obtained by extraction and stored in the form of encapsulation powder. This study has two purposes, (i) to know the effect of the gelatin and maltodextrin encapsulants ratio on the encapsulates characteristics of papaya leaf coloring extract, and (ii) to determine the encapsulates comparison treatment of the best gelatin and maltodextrin in producing the characteristic encapsulate extract of papaya leaf coloring. Experiments in this study were  using a randomized block design with one  treatment, namely the ratio of gelatin and maltodextrin consisting of 7 levels, namely, (1:0), (0:1) (1:1), (1:1.5), (1:2), (1:2.5), (1:3). The results showed that the ratio of gelatin-maltodextrin was highly significant (P<0.05) on yield, total chlorophyll content, solubility, brightness level, redness level (a*), yellowish level (b*) and no effect (P>0.05) on water content. The treatment of gelatin and maltodextrin (1:3) ratio was the best treatment to produce encapsulate sea lettuce extract with yield of 35.27 %, water content of 6.13%, total chlorophyll content of 1192.69 ppm, solubility of 79.12%, brightness level (L*) 39.39, redness level (a*) 16.95 and yellowish level (b*) 14.84. Keywords : papaya leaf extract, gelatin, maltodextrin, encapsulation